The new hybrid value at risk approach based on the extreme value theory - Radivojević, Nikola; Cvjetković, Milena; Stepanov, Saša (Estudios de Economía, 2016)
In this paper the authors introduce a new hybrid approach based on the Extreme Value Theory (EVT) to joint estimation of Value at Risk (VaR) and Expected Shortfall (ES) for high quantiles of return distributions. The approach is suitable for measuring market risk in the emerging markets. It is designed to capture the empirical features of returns with emerging markets, such as leptokurtosis, asymmetry, autocorrelation and heteroscedasticity.